Beyond the thale: comparative genomics and genetics of Arabidopsis relatives - Koenig, Daniel; Weigel, Detlef (Nature reviews. Genetics, 2015)
Key Points Although Arabidopsis thaliana has traditionally been the primary model organism in plants, several closely related species have recently become a focal point for comparative genomic studies and have led to an expansion of the spectrum of traits under study. The availability and analysis of several high-quality whole-genome sequences from species closely related to A. thaliana within the Brassicaceae family have shed light on the processes of genome evolution in plants, including the emergence and evolution of polyploids. Comparative genomic studies across species of the Brassicaceae family have identified an important role for local gene duplications and deletions in generating evolutionary diversity and diversification of gene function in plants. Several species of the Brassicaceae family are better subjects for field studies than A. thaliana itself. The use of these species as models has enabled researchers to identify the genetic basis for fitness in the real field conditions. The accelerated production of high-quality whole-genome sequences from a range of plant species, and the emergence of genome-editing technologies, will continue to facilitate advances in the study of non-model species in the Brassicaceae family. Arabidopsis thaliana , a member of the phenotypically diverse Brassicaceae family, has proved to be a key model organism for characterizing plant genome and morphological evolution. This Review outlines how recent comparative and functional genomic studies using Arabidopsis relatives have further advanced our understanding of plant diversity and evolution. For decades a small number of model species have rightly occupied a privileged position in laboratory experiments, but it is becoming increasingly clear that our knowledge of biology is greatly improved when informed by a broader diversity of species and evolutionary context. Arabidopsis thaliana has been the primary model organism for plants, benefiting from a high-quality reference genome sequence and resources for reverse genetics. However, recent studies have made a group of species also in the Brassicaceae family and closely related to A. thaliana a focal point for comparative molecular, genomic, phenotypic and evolutionary studies. In this Review, we emphasize how such studies complement continued study of the model plant itself, provide an evolutionary perspective and summarize our current understanding of genetic and phenotypic diversity in plants.